ESTUDO ANALÍTICO E AVALIAÇÃO DA ATIVIDADE LARVICIDA DA MISTURA DOS ÓLEOS ESSENCIAIS DAS FOLHAS DA Pimenta dioica Lindl E DOS GALHOS DE Aniba duckei Kostermans FRENTE AO MOQUISTO Aedes Aegypti (LINNAEUS, 1762) - Pereira, Aldemir da Guia Schalcher (2009)
In the search for alternative chemical control against Aedes aegypti L., various studies are developed and encouraged in order to find new substances insecticidal plant and in this context essential oils have been shown to be very promising. Extracted from the essential oils of species Lindl Pimenta dioica (leaves) and Aniba duckei Kostermans (stems) by means of hydrodistillation using a Clevenger system and promoted its mixture of equal parts. In this study, the larvicidal effect of the mixture of essential oils extracted from leaves of Pimenta dioica species Lindl and branches of Aniba duckei Kostermans were evaluated against the mosquito Aedes aegypti (Linnaeus, 1792). The blend of essential oils obtained were carried out analysis of constant physical and chemical density (0.904 g mL-1), refractive index (ND 25 = 1.379), solubility in 70% ethanol (1:2), color (yellow) and appearance (clear). Its components were identified by Gas Chromatography Mass Spectrometry (GC-MS). We identified and quantified by the method of standard components, myrcene (2.36%), limonene (1.00%), linalool (63.04%), myrcenol (1.13%), alilfenol (1, 40%) and eugenol (31.07%). The blend of essential oils and patterns of eugenol and linalool were tested in five concentrations: 20, 50, 70, 90 and 100 μg mL-1. The LC50 of the mixture of essential oils and the limits of confidence at 95% probability were calculated by the methods of Reed-Muench and Pizzi, respectively. The larvicidal activity was observed based on the percentage of dead larvae, the action was assessed 24h after treatment. The blend of essential oils had larvicidal activity with LC50 of 113,95 (±2.11) μg mL-1 and the patterns of eugenol 90,86 (±0,03) μg mL-1 and linalool 305,42 (±0,03) μg mL-1. The results indicate that the mixture of essential oils evaluated, is composed of substances that together with the major components eugenol and linalool provided greater larvicidal effect against the mosquito Aedes aegypti L.